KRÆFTPATIENTERS BRUG AF REIKI-HEALING SOM MAGISK PRAKSIS - Boelsbjerg, Hanne Bess (Tidsskriftet Antropologi, 2010)
Almost half the number of Danish cancer patients are involved in alternative or complementary treatments while receiving conventional cancer treatment. reikihealing is one of the alternative treatments they often seek out. It is a treatment that has a spiritual and holistic approach to both the person and the illness, claiming to transmit energy from the hands of the healer to the one being healed. This creates a contradiction with the concurrent use of conventional treatment which rests on a biomedical understanding of cause and effect. In this context, the use of reikihealing can be regarded as a kind of magical practice by cancer patients, who might not necessarily share the same underlying worldview as the reiki-healer. The basis for this article is a qualitative study called ‘Reiki-healing as Experienced by Cancer Patients’, undertaken at the University of Copenhagen and financed by the Danish Cancer Foundation. Here the cancer patients reported their experiences during reiki-healing and were asked to describe how they understood the treatment and what effects it had for them. Most of them referred to the healer as a gifted person who has the power to influence their minds and bodies or, notably, the way they conceive of themselves. These statements support the interpretation of reiki-healing as a magical practice, which is characterized by the placement of a magical agency as one of the components of a ritual – in this case, the healer. If the cancer patient shares the same holistic approach as the healer, the use of reiki-healing can turn out to be a spiritual or religious coping strategy, which helps the person to find meaning and support in times of crisis. In both examples, reiki-healing is used as a magical practise because of the opportunity it offers to influence the illness and life situation, which otherwise would be beyond the reach of conventional medicine. Keywords: Healing, reiki, religious coping, healing ritual, cancer